2014
DOI: 10.1063/1.4902242
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of core-shell structured polyaniline at helical carbon nanotube hybrids for ammonia gas sensor

Abstract: Articles you may be interested inEnhanced dielectric performance of three phase percolative composites based on thermoplastic-ceramic composites and surface modified carbon nanotube Appl. Phys. Lett. 106, 012902 (2015); 10.1063/1.4904937 Physisorption-induced electron scattering on the surface of carbon-metal core-shell nanowire arrays for hydrogen sensing Appl. Phys. Lett. 102, 233111 (2013); 10.1063/1.4811165 Spectroscopic investigations of ammonia gas sensing mechanism in polypyrrole nanotubes/nanorods J. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Fluorescence with no significant loss in intensity during cyclical switching (on and off) of NH 3 gas indicated the stability and fast responsive behavior of (OA) 2 PbI 4 . Formation of volatile methylamine makes conventional MAPbI 3 unstable to withstand continuous exposure cycles of NH 3 and changes its property irreversibly after the first pulse of NH 3 , whereas formation of low volatile OA in the presence of NH 3 and reconversion to octylammonium in the absence of NH 3 makes (OA) 2 PbI 4 an interesting room temperature sensory material for NH 3 (Figure B­(i)). , Interestingly, (OA) 2 PbI 4 did not show response or changes in properties in the presence of water vapor, as established by fluorescence spectroscopy and optical microscopy (Figure A,B). The green fluorescence of the (OA) 2 PbI 4 film showed no changes during the exposure or removal of water vapor (Figure B), which proved the sensitivity of (OA) 2 PbI 4 specifically toward NH 3 and not toward atmospheric moisture.…”
Section: Results and Discussionmentioning
confidence: 93%
“…Fluorescence with no significant loss in intensity during cyclical switching (on and off) of NH 3 gas indicated the stability and fast responsive behavior of (OA) 2 PbI 4 . Formation of volatile methylamine makes conventional MAPbI 3 unstable to withstand continuous exposure cycles of NH 3 and changes its property irreversibly after the first pulse of NH 3 , whereas formation of low volatile OA in the presence of NH 3 and reconversion to octylammonium in the absence of NH 3 makes (OA) 2 PbI 4 an interesting room temperature sensory material for NH 3 (Figure B­(i)). , Interestingly, (OA) 2 PbI 4 did not show response or changes in properties in the presence of water vapor, as established by fluorescence spectroscopy and optical microscopy (Figure A,B). The green fluorescence of the (OA) 2 PbI 4 film showed no changes during the exposure or removal of water vapor (Figure B), which proved the sensitivity of (OA) 2 PbI 4 specifically toward NH 3 and not toward atmospheric moisture.…”
Section: Results and Discussionmentioning
confidence: 93%
“…339 The sensitivity of this system of SWCNT-PABS can achieve a NH 3 LOD of 100 ppb (20 ppb for NO 2 ) by adjusting the initial resistance of the sensor. 141 In addition, composites of poly(aniline) (PANI) and CNTs, prepared by electropolymerization on SWCNT electrodes 340 or by in situ polymerization of aniline in SWCNT suspension, 341,342 showed low limits of detection to NH 3 (50 ppb Zhang et al 340 ) and fast recovery times. Interestingly, Li et al reported that poly(methyl methacrylate) (PMMA) when combined with MWCNTs produced n-type gas sensing characteristics with a decrease in resistivity when exposed to NH 3 .…”
Section: Cnt-based Sensors For Environmental Monitoringmentioning
confidence: 99%
“…However, they still have limitations, such as a low selectivity and long response and recovery times compared to metal oxide- or CP-based sensors [ 25 , 26 , 27 , 28 ]. Regarding these issues, there have been some results improved by surface treatments [ 16 , 29 , 30 ], functionalization [ 19 , 31 , 32 , 33 ], the use of core-shell structures [ 34 , 35 ], specially designed hetero-structures [ 36 , 37 ], etc.…”
Section: Introductionmentioning
confidence: 99%